476 AK119, a humanized anti-CD73 monoclonal antibody, as Immunotherapy for COVID-19. (9th November 2020) - Zhong, Tingting; Huang, Zhaoliang; Pang, Xinghua; Chen, Na; Kwek, Konyew; Wynne, Chris; Konpa, Adam; Jin, Xiaoping; Xia, Yu; Wang, Maxwell Zhongmin; Li, Baiyong; Xia, Yu
Abstract : Background: CD73, an ecto-5'-nucleotidase involved in ATP metabolism, converts AMP into adenosine. ATP could induce production of interferon-beta 1, which induces cellular resistance to viral infection and triggers apoptosis of virus-infected cells. 2 In COVID-19, SARS-CoV-2 causes severe respiratory syndrome by effectively inhibiting interferon activity, 3 4 leading to impaired anti-viral response. Moreover, lung injury seen in severe COVID-19 patients might be caused by excess adenosine. 5 Inhibition of CD73 is believed to increase extracellular ATP, thereby countering COVID-19. Furthermore, independent of its inhibitory effects on CD73, preclinical results from other anti-CD73 mAb suggested CD73 blockade activates lymphocytes, induced antibody production from B cells and enhanced lymphocyte trafficking, 6 thereby, stimulated the production of anti-SARS-CoV-2 antibodies leading to the rapid clearance of the virus. 7 We developed AK119, a humanized monoclonal antibody targeting CD73, as an immunotherapy agent for the treatment of COVID-19. Methods: Evaluation of AK119 activity to bind to the CD73 antigen was performed by using ELISA, Fortebio, and FACS assay. The activity of AK119 to inhibit enzymatic activity of CD73 was evaluated by cell-based enzyme assay; and the activity of AK119 to induce internalization of CD73 and enhance CD69 and CD83 expression on B cell were performed by using FACS assays. We also investigated the potential of AK119 to promote immunoglobulin production from human B cells. Results: AK119 could effectively bind to human CD73 with high affinity, which is comparable or superior to 10.3AA, a leading anti-CD73 antibody, in protein-based assays. AK119 inhibited CD73 enzymatic activity on MDA-MB-231 cells (IC50_AK119, 27.60 nM; IC50_10.3AA, 15.99 nM) and U87-MG cells (IC50_AK119, 0.2448 nM; IC50_10.3AA, 0.0691 nM), with a higher maximal inhibition rates of 108.26% in MDA-MB-231 cells and 96.24% in U87-MG cells compared with 10.3AA (77.02% and 75.77%, respectively). AK119 effectively induced CD73 internalization in MDA-MB-231 cells and U87-MG cells, and the internalization rate of CD73 was 60.75% and 82.39%, respectively; for 10.3AA, the internalization rate was 50.53% and 73.65%, respectively. Moreover, AK119 could stimulate approximately 4–5 fold up-regulation of CD69 (figure 1A) and CD83 (figure 1B) that are markers of B cell activation; and, AK119 significantly promoted IgG production from B cells. Conclusions: In summary, in comparison to a leading CD73 antibody currently in clinical trial, AK119 demonstrated more complete CD73 inhibition; and more dramatic B cell activation and antibody production. Thus, A119 presented desirable preclinical bioactivities. The safety and pharmacokinetics of single ascending doses of AK119 will be evaluated in healthy volunteers in an upcoming Phase 1, First-in-Human study (NCT04516564 ). Trial Registration: NCT04516564 References: Zhang C, He H, Wang L, et al. Virus-Triggered ATP release limits viral replication through facilitating IFN-β production in a P2X7-dependent manner. J Immunol 2017;199:1372–1381. Schneider WM, Chevillotte MD, Rice CM. Interferon-stimulated genes: a complex web of host defenses. Annu Rev Immunol 2014;32:513–545. Hadjadj J, Yatim N, Barnabei L, et al. Impaired type I interferon activity and inflammatory responses in severe COVID-19 patients. Science 2020;369:718–724. Yuen CK, Lam JY, Wong WM, et al. SARS-CoV-2 nsp13, nsp14, nsp15 and orf6 function as potent interferon antagonists. Emerg Microbes Infect 2020;9:1418–1428. Hoogendijk AJ, Pinhanços SS, van der Poll T, Wieland CW. AMP-activated protein kinase activation by 5-aminoimidazole-4-carbox-amide-1-β-D-ribofuranoside (AICAR) reduces lipoteichoic acid-induced lung inflammation. J Biol Chem 2013;288:7047–7052. Luke, Jason J., et al. Immunobiology, preliminary safety, and efficacy of CPI-006, an anti-CD73 antibody with immune modulating activity, in a phase 1 trial in advanced cancers. J Clin Oncol 2019;37: suppl 2505–2505. Corvus Pharmaceuticals, Inc. Corvus Pharmaceuticals Provides Business Update and Reports Second Quarter 2020 Financial Results. 30 July 2020. [https://corvuspharma.gcs-web.com/news-releases/news-release-details/corvus-pharmaceuticals-provides-business-update-and-reports-4].